Flipped Micro-Modules for Teaching Sustainable Engineering Practices - Huiying (Cynthia) Hou; Haoran Zhang; Yishan Wang (Education Sciences, 2023)
With the aim of assisting students in acquiring the practical knowledge required for sustainable engineering practices, a new intervention method in the form of flipped micro-modules was developed. The perceived quality of the flipped micro-modules and their relationship with the students’ attitudes towards using them were then evaluated using an extended technology acceptance model (TAM-extended model). The quality of the flipped micro-modules was measured based on three aspects: the quality of the framework, the quality of the content, and the quality of the operation. The findings revealed that the students considered the framework of the flipped micro-modules to be the most important aspect. The findings also demonstrated that the flipped micro-modules have the potential to improve engineering education and prepare students for future sustainable engineering practices.